Trophic status analysis and estimation of fish production in Aneuk Laot Lake aquatic resources management, Sabang City - Nurfadillah Nurfadillah; Irma Dewiyanti; Sri Riska Rahayu; Siswani Sari; Indri Karina; Hasfiandi Hasfiandi (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2022)
Aneuk Laot Lake is located in Sabang City, Weh Island, Aceh Province. Changes in water quality can affect the life of aquatic organisms found in Aneuk Laot Lake. The purpose of this research estimates fish production and trophic status for the aquatic resource management of Aneuk Laot Lake, Sabang. This research was conducted in September 2019 in Lake Aneuk Laot using the TRIX, TSI (Trophic State Index) and Nygaard index methods to determine fish production and trophic status. Observation stations were determined using stratified random sampling method and analysis of chlorophyll-a was done using the Trichomatic method. The results showed that the waters of Aneuk Laot Lake can be categorized as eutrophic to hypereutrophic. The estimated value of fish production in Aneuk Laot Lake based on the chlorophyll-a approach is 109.84 kg/ha/year, with a lake area of 61.6 ha. Water quality parameters are still in a state that can be tolerated by aquatic organisms in Aneuk Laot Lake.Keywords:Fish production potential Water qualityTRIX indexBiomass productionWater productivity